PERAN EFIKASI DIRI, PERSEPSI HUMAN RESOURCE MANAGEMENT PRACTICES (HRMP) TERHADAP INOVASI KERJA DENGAN SUKSES KARIR - Sri Hayati (Universitas Ahmad Dahlan, 2015)
Abstract The competitiveness of an organization is determined by innovation at the level of organizations, groups and individuals. Individual innovation is essential for organizational success. This study is aimed to look at the role of self efficacy, perceptions of HRMP and career success towards work innovation. This research was quantitative explanation, that examined the role between variables in the hypothesis. This research used a scale of self efficacy, perceptions of HRMP, career success and work innovation. The subject were 115 employees from PT BBM in Makassar. The method of analysis used structural equation modeling (SEM). Analysis result showed that: (1) self efficacy had positive and ignificanteffect towards work innovation, which value was 0,325, (2) self efficacy had positive and significant effect on the work innovation, with career success as mediating variable, which value was 0,094, (3) perception of HRMP have positif and significant effect on work innovation, which value was 0,354 (4) perception of HRMP had positif and significant effect on work innovation, with career success as mediating variable, which value was 0,074. Hence, the variables which can be the predictors of the work innovation are self efficacy, perception of HRMP and career success. Keyworks: career success, self efficacy, work innovation